Witness the Dead - Robertson, Craig, 1944- (London Simon & Schuster, 2013)
Scottish Police are called to a murder scene in Glasgow's Northern Necropolis. The body of a young woman lies stretched out over a tomb in what looks like a ritualistic murder. Her body bears a three letter message from her killer, daubed in lurid red lipstick. In the 1970s, Danny Neilson was the detective working on the infamous Red Silk murders. Still haunted by the memory of the unsolved investigation, he spots a link between the new murders and those carried out by Red Silk - details that no copycat killer could have known about. But Archibald Atto, the man suspected of the killings all those years ago, is rotting in jail, so Danny has to face up to his fear that they never caught their man. Neilson goes with police photographer Tony Winter, to visit Archibald Atto in prison. But Atto will not speak to them unless it is on his terms. As clues begin to surface, they learn that they are dealing with a killer whose agenda is so terrifying and history so twisted that it will take the combined efforts of police forces past and present to make an arrest.
Keywords: Murder--Investigation